Currency Convertibility and the Fund : Review and Prognosis - Galbis, Vicente (Washington, D.C. : International Monetary Fund, 1996)
This paper reviews experience with currency convertibility on both the current and capital accounts, with particular attention to the Fund's concepts and policy implications. After discussing the basic concepts of convertibility, the paper reviews the experience with convertibility in three groups of Fund members--industrial countries, developing countries, and transition countries. The paper also discusses some policy options designed to encourage acceptance of convertibility by Fund members that have not yet done so.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet